Intelligent simulation of printed circuit board manufacture and assembly - Chong, Chin Soon. (2009)
ISE — Intelligent Simulation Environment, an integrated framework that supports printed circuit board manufacturing simulation, has been designed and developed. This environment addresses problems encountered by manufacturing engineers, with no or little experience, in using simulation. In this tool, simulation models are defined in terms of graphical objects, which correspond to the actual manufacturing components. The user defined data is then interpreted and compiled by the program to simulation language codes, which can subsequently be run to obtain simulation output. The output, and the production data is used by the program for diagnosis and treatment of manufacturing problems.